Painting Beyond Itself: The Medium in the Post-Medium Condition, Isabella Graw and Ewa Lajer-Burcharth (eds) (2016). (1st October 2019) - Green, Alison
Painting Beyond Itself: The Medium in the Post-Medium Condition, Isabella Graw and Ewa Lajer-Burcharth (eds) (2016)Berlin: Sternberg Press, 292 pp., ISBN 978-3-95679-007-2, p/bk, £13.95